‘To be ashamed.’ On the meaning and theological fruit of a phenomenology of negative self-awareness - Slenczka, N (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Over the course of this presentation, I will simply work through each of the elements of my title. I will first explain what phenomenology is. Then I will make some phenomenological remarks about shame – that is the longest section. Then I will have a brief summary of what was achieved, in which I will present a thesis – or better, a generalizing supposition – regarding what one experiences about human self-awareness in the phenomenon of shame. Then, finally, I will turn to the theological fruit.